Activity-dependent plasticity of mouse hippocampal assemblies in vitro - Keller, Martin K.; Draguhn, Andreas; Both, Martin; Reichinnek, Susanne (Frontiers in Neural Circuits, 2015)
Memory formation is associated with the generation of transiently stable neuronal assemblies. In hippocampal networks, such groups of functionally coupled neurons express highly ordered spatiotemporal activity patterns which are coordinated by local network oscillations. One of these patterns, sharp wave-ripple complexes (SPW-R), repetitively activates previously established groups of memory-encoding neurons, thereby supporting memory consolidation. This function implies that repetition of specific SPW-R induces plastic changes which render the underlying neuronal assemblies more stable. We modeled this repetitive activation in an in vitro model of SPW-R in mouse hippocampal slices. Weak electrical stimulation upstream of the CA3-CA1 networks reliably induced SPW-R of stereotypic waveform, thus representing re-activation of similar neuronal activity patterns. Frequent repetition of these patterns (100 times) reduced the variance of both, evoked and spontaneous SPW-R waveforms, indicating stabilization of pre-existing assemblies. These effects were most pronounced in the CA1 subfield and depended on the timing of stimulation relative to spontaneous SPW-R. Additionally, plasticity of SPW-R was blocked by application of a NMDA receptor antagonist, suggesting a role for associative synaptic plasticity in this process. Thus, repetitive activation of specific patterns of SPW-R causes stabilization of memory-related networks.